Restoration of abandoned agricultural lands toward habitats for umbrella species - Nekhay, O.; Arriaza, Manuel (Instituto Nacional de Investigación y Tecnología Agraria y Alimentaria (INIA), 2009)
This study analyzes the suitability of agricultural lands with risk of abandonment for restoration to suitable habitats for animal species of conservation interest. As a case study, the main focus was on olive plantations (Olea europaea L.) of mountainous areas of Southern Spain and the Iberian lynx (Lynx pardinus Temminck, 1827). The method weighs the judgement of experts on the effect of landscape elements on the habitat via an analytic hierarchy process and spots areas most suitable for restoration through geographical information systems. The results suggest that the edge of major agricultural areas and areas with natural vegetation adjacent to the Natural Park of Sierra de Cardeña and Montoro would be most suitable for restoration of the lynx habitat. The precise location of olive groves suitable for restoration are discussed, as revealed by experts decision-making processes. The main interest of the study relies on the potential of the method to combine territorial analysis with biological requirements of endangered species to facilitate their dispersal. El presente estudio analiza la idoneidad de zonas agrícolas con riesgo de abandono para su restauración como hábitat de especies animales de interés. Como caso de estudio se considera las plantaciones olivareras (Olea europaea L.) de montaña del sur de España y el lince ibérico (Lynx pardinus). La metodología pondera la opinión de un grupo de expertos sobre el efecto que los diferentes elementos del paisaje tienen sobre el hábitat del lince, integrándose posteriormente en un sistema de información geográfica. Los resultados sugieren que las zonas olivareras lindantes con el Parque Natural de la Sierra de Cárdena y Montoro y zonas con vegetación natural existente serían las más adecuadas para su restauración. Si bien la exacta localización de las zonas más adecuadas está sujeta a discusión, como demuestran las divergencias en la opinión de los expertos, el interés principal del estudio radica en la potencialidad del enfoque metodológico, el cual combina ...